Off-road diesel engine transient response improvement by electrically assisted turbocharging - Terdich, N; Martinez-Botas, R; Howey, D; Copeland, C; Costall, A (2011)
Turbocharged diesel engines are widely used in off-road applications including construction and mining machinery, electric power generation systems, locomotives, marine, petroleum, industrial and agricultural equipment. Such applications contribute significantly to both local air pollution and CO 2 emissions and are subject to increasingly stringent legislation. To improve fuel economy while meeting emissions limits, manufacturers are exploring engine downsizing by increasing engine boost levels. This allows an increase in IMEP without significantly increasing mechanical losses, which results in a higher overall efficiency. However, this can lead to poorer transient engine response primarily due to turbo-lag, which is a major penalty for engines subjected to fast varying loads. To recover transient response, the turbocharger can be electrically assisted by means of a high speed motor/generator. When the engine load is increased, the electrical machine acts as a motor to accelerate the turbocharger so that the torque demand can be met rapidly. Conversely, when boost delivery exceeds demand the electrical machine can act as a generator to recover energy that would otherwise be wastegated. This paper presents a model for the transient response of the electrically-assisted turbocharged engine when subjected to a step increase of torque demand. The base model is representative of a 7-litre turbocharged intercooled diesel engine and has been implemented in Matlab-Simulink and calibrated against test bed data. The model is used for the analysis of the dynamic behaviour of the engine with different levels of electric assist to the turbocharger. The results show that while turbocharger response improves with electric assist, compressor surge can occur in generating mode and that limitations on electric assist power are present. Copyright © 2011 SAE International.